DETERMINANTS OF MENTAL HEALTH LITERACY AMONG ADOLESCENTS: A CROSS-SECTIONAL STUDY - Juniarni, Lia; Ridwan, Andre Aulia (DPW PPNI Provinsi Jawa Barat, 2025)
Background: According to the World Health Organization, approximately 450 million people worldwide experience mental health issues, with 14.4% attributed to behavioral contributors and 13.5% categorized as mental health problems (Ministry of Health of the Republic of Indonesia, 2018). Adolescents from lower socioeconomic backgrounds are more likely to engage in unhealthy behaviors and demonstrate lower levels of health literacy. This study aims to identify the factors associated with mental health literacy in adolescents, with particular focus on peer pressure and economic inequality. Methods: This quantitative descriptive study employed a cross-sectional design. A total of 539 adolescents aged 10–19 years participated in the study through online questionnaires distributed via smartphones. Instruments used included the Mental Health Literacy–Young Adult Questionnaire, the International Wealth Index (IWI), and the Peer Pressure Scale. Respondents were selected using a convenience sampling technique. Data were analyzed using Pearson correlation, Spearman test, independent t-test, and linear regression. Results: The majority of respondents (60.1%) were male and enrolled in junior or senior high school. Bivariate analysis indicated significant associations between mental health literacy and peer pressure, economic disparity, age, gender, and education level (p < 0.05). However, multivariate analysis revealed that only economic disparity and gender remained significantly associated with mental health literacy, while peer pressure, age, and education level did not show linear relationships. Conclusion: Economic inequality and gender are significant factors influencing mental health literacy in adolescents. These findings highlight the need for targeted interventions to reduce socioeconomic disparities and promote gender-sensitive mental health education.